HBx mutations promote hepatoma cell migration through the Wnt/β‐catenin signaling pathway. Issue 10 (1st September 2016) - Chen, Zhen; Tang, Jia; Cai, Xuefei; Huang, Yao; Gao, Qingzhu; Liang, Li; Tian, Ling; Yang, Yi; Zheng, Yaqiu; Hu, Yuan; Tang, Ni
Abstract : HBx mutations (T1753V, A1762T, G1764A, and T1768A) are frequently observed in hepatitis B virus (HBV)‐related hepatocellular carcinoma (HCC). Aberrant activation of the Wnt/β‐catenin signaling pathway is involved in the development of HCC. However, activation of the Wnt/β‐catenin signaling pathway by HBx mutants has not been studied in hepatoma cells or HBV‐associated HCC samples. In this study, we examined the effects of HBx mutants on the migration and proliferation of HCC cells and evaluated the activation of Wnt/β‐catenin signaling in HBx‐transfected HCC cells and HBV‐related HCC tissues. We found that HBx mutants (T, A, TA, and Combo) promoted the migration and proliferation of hepatoma cells. The HBx Combo mutant potentiated TOP‐luc activity and increased nuclear translocation of β‐catenin. Moreover, the HBx Combo mutant increased and stabilized β‐catenin levels through inactivation of glycogen synthase kinase‐3β, resulting in upregulation of downstream target genes such as c‐Myc, CTGF, and WISP2 . Enhanced activation of Wnt/β‐catenin was found in HCC tissues with HBx TA and Combo mutations. Knockdown of β‐catenin effectively abrogated cell migration and proliferation stimulated by the HBx TA and Combo mutants. Our results indicate that HBx mutants, especially the Combo mutant, allow constitutive activation of the Wnt signaling pathway and may play a pivotal role in HBV‐associated hepatocarcinogenesis. Abstract : Our results indicate that HBx mutants, especially the Combo mutant, allow constitutive activation of the Wnt signaling pathway and may play a pivotal role in HBV‐associated hepatocarcinogenesis.